Ataxia Telangiectasia-Mutated (ATM)Polymorphisms and Risk of Lung Cancer in a Chinese Population - Myneni, Ajay A.; Chang, Shen-Chih; Niu, Rungui; Liu, Li; Zhao, Baoxing; Shi, Jianping; Han, Xiaoyou; Li, Jiawei; Su, Jia; Yu, Shunzhang; Zhang, Zuo-Feng; Mu, Lina (Frontiers in Public Health, 2017)
Background: The ataxia telangiectasia mutated (ATM) gene has a key role in DNA repair including activation and stabilization of p53, which implicates the importance of ATM polymorphisms in the development of cancer. This study aims to investigate the association of two ATM single nucleotide polymorphisms (SNPs) with lung cancer, as well as their potential interaction with p53 gene and other known risk factors of lung cancer. Methods: A population-based case-control study was conducted in Taiyuan city, China with 399 cases and 466 controls matched on the distribution of age and sex of cases. The two ATM gene SNPs, ATMrs227060 and ATMrs228589 as well as p53 gene SNP, p53rs1042522 were genotyped using Sequenom platform. Unconditional logistic regression models were used to estimate crude and adjusted odds ratios (aOR) and 95% confidence intervals (CIs). Adjusted models controlled for age, sex and smoking status. Results: The study showed that TT genotype of ATMrs227060 (aOR = 1.58, 95% CI: 1.06–2.35) and AA genotype of ATMrs228589 were significantly associated with lung cancer (aOR = 1.50, 95% CI: 1.08–2.08) in a recessive model. Additionally, carrying variant genotypes of ATMrs227060(TT), ATMrs228589(AA) and p53rs1042522(CC) concomitantly was associated with much higher risk (aOR = 3.68, 95% CI: 1.43–9.45) of lung cancer than carrying variant genotypes of any one of the above three SNPs. We also found multiplicative and additive interaction between tea drinking and ATMrs227060 in association with lung cancer. Conclusions: This study indicates that ATM gene variants might be associated with development of lung cancer in Chinese population. These results need to be validated in larger and different population samples.